Segmentation of geospatial rasters: analysis of the temporal characteristics of the AREAONAREAOVERLAYER algorithm - Tsaryniuk, O.V.; Glybovets, A.M. (PROBLEMS IN PROGRAMMING, 2025)
This paper investigates the performance of the AreaOnAreaOverlayer algorithm used for segmenting geospatial rasters based on elevation features within the FME environment. The main focus is on analyzing the algorithm’s temporal characteristics when processing large volumes of data, particularly in vegetation cover classification tasks. The study describes the experimental setup, typical input data, and the impact of polygon geometric parameters on execution time. The results provide insight into the algorithm’s application limits and reveal dependencies between the structure of input data and computational complexity.Prombles in programming 2025; 2: 87-97